Isolation and Identification of Indigenous Yeast Strain and Its Potential for Yeast Extract Production - Mahilrajan, S.; Emmanuel, C. J.; Srivijeindran, S. (University of Jaffna, 2021)
The growing demand for protein-rich food forces humans to search for alternative protein sources. Yeasts are among the preferred candidates due to their well-balanced source of amino acids and vitamins. The present study aimed to identify an indigenous yeast strain that can be used as a protein source. Yeast strains were isolated from Palmyrah toddy sediments collected from different regions in the Jaffna Peninsula. One yeast strain, named A3, was selected as a potential strain based on the maximum cell size and optical density among the 55 yeast strains isolated. The biochemical analysis and sequencing of the ITS region (including 5.8S rRNA gene) and the LSU rRNA gene D1/D2 domains confirmed the yeast isolate as a strain of Saccharomyces cerevisiae. The optimum growth conditions for the yeast strain were determined using Taguchi L16 orthogonal array. Yeast cell autolysis was conducted with and without papain, and the yield of soluble matter and total protein were measured. The strain yielded a maximum of 70.7 % soluble mater and 56.9 % of total protein when autolysis with papain. The yield is significantly higher (p<0.05) than obtained with the baker's yeast used in the control experiment.
Keywords: Palmyrah toddy; Saccharomyces cerevisiae; Single-cell protein; Yeast